Approach with Primer Percutaneous Coronary Intervention to Acute Anterior Myocardial Infarction in Patient with Dextrocardia - Akbulut, M.; Cakmak, T.; Cihangiroglu, A.; Yavuzkir, M. F.; Mirzaoglu, C.; Harman, M. (Excerpta Medica Inc-Elsevier Science Inc, 2014)
[Abstract Not Available]